The index endoscopic characteristics associated with gastric neoplasms in serial screening of upper gastrointestinal endoscopy - Jung Huh; Su Hwan Kim; Kwang Woo Kim; Yun Jin Jeong; Dong Jun Oh; Dong Kee Jang; Heejoon Jang; Ji Bong Jeong; Ji Won Kim; Kook Lae Lee; Hyoun Woo Kang (The Saudi Journal of Gastroenterology)
Background: Although biennial upper gastrointestinal endoscopy is recommended for gastric cancer screening in Korea, data regarding the endoscopic characteristics associated with the diagnosis of gastric neoplasms in serial endoscopic screening are limited. We aimed to evaluate the index endoscopic characteristics associated with the diagnosis of gastric neoplasms and adequate gastric cancer screening interval. Methods: We retrospectively reviewed cases of the patients diagnosed with gastric neoplasms, who showed no evidence of gastric neoplasms on index endoscopy between October 2005 and December 2022. The indices of endoscopic characteristics were analyzed. Patients were stratified according to the interval between endoscopic examinations (≤1, 1–2, 2–3, and >3 years), and the proportion of adenoma, early gastric cancer (EGC) and advanced gastric cancer (AGC) was analyzed across groups. Results: A total of 331 lesions with histological diagnoses of gastric neoplasms (167 adenomas, 138 EGCs, and 26 AGCs) were included. The initial baseline endoscopic findings were as follows: normal, 22 (6.7%); gastritis, 16 (4.8%); erosion, 65 (19.6%); ulcers, 19 (5.8%); atrophy, 104 (31.4%); and intestinal metaplasia, 105 (31.7%). The proportion of AGC increased with longer surveillance intervals: 0% at ≤1 year (median: 0.76 years, interquartile range [IQR]: 0.38), 3.1% at 1–2 years (1.59; 0.57), 6.7% at 2–3 years (2.37; 0.51), and 20.0% at >3 years (4.18; 1.53). Conversely, adenoma were most frequently detected within 1 year, comprising 63.6% (P < 0.05). Conclusion: Cautious follow-up endoscopy may be necessary for patients demonstrating endoscopic findings of atrophy and intestinal metaplasia. Shorter surveillance intervals enable early detection of gastric neoplasia and may prevent progression to advanced cancer.